1996
DOI: 10.1016/s0886-3350(96)80046-0
|View full text |Cite
|
Sign up to set email alerts
|

Topical versus peribulbar anesthesia in clear corneal cataract surgery

Abstract: Topical anesthesia is a safe, effective alternative to peribulbar anesthesia in clear corneal cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 10 publications
2
38
0
3
Order By: Relevance
“…It is now a widely accepted procedure and has become a wellestablished technique in phacoemulsification surgery as an alternative to the retrobulbar and peribulbar techniques. [2][3][4][5][6][7] Because it is less invasive, reducing the risk of complications and eliminating complications from needle and systemic toxicity, topical anaesthesia has gained popularity among surgeons. [8][9][10] Topical anaesthesia confers the advantages of relatively faster visual recovery and higher patient satisfaction, easy application, minimal discomfort on administration, rapid onset of anaesthesia, and lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…It is now a widely accepted procedure and has become a wellestablished technique in phacoemulsification surgery as an alternative to the retrobulbar and peribulbar techniques. [2][3][4][5][6][7] Because it is less invasive, reducing the risk of complications and eliminating complications from needle and systemic toxicity, topical anaesthesia has gained popularity among surgeons. [8][9][10] Topical anaesthesia confers the advantages of relatively faster visual recovery and higher patient satisfaction, easy application, minimal discomfort on administration, rapid onset of anaesthesia, and lower cost.…”
Section: Introductionmentioning
confidence: 99%
“…A study comparing proximetacaine with 0.5% tetracaine in patients undergoing phacoemulsification with incision without sutures, in forty patients selected randomly, the authors observed that the incidence of complaints of discomfort (pricking or stinging sensation) was lower in patients who used proximetacaine than in patients who used tetracaine, and this difference was statistically significant, but there was no loss in analgesic effect 34 . Proximetacaine has lower corneal toxicity than 0.4% oxybuprocaine and 2% and 4% lidocaine 35,36 . In the present study, 42 patients complained of intraoperative pain, which represented 13.5% of the patients and is different than that reported in the literature that describes a higher incidence, around 60% of the patients undergoing fasciectomy with topical anesthesia without sedation and similar to the studies with retrobulbar 37 and peribulbar 38 anesthesia.…”
Section: Discussionmentioning
confidence: 92%
“…Em estudo comparativo do uso desse anestésico com a tetracaína a 0,5% em pacientes submetidos à facoemulsificação com incisão sem sutura, em 40 pacientes selecionados aleatoriamente, autores observaram que naqueles que usaram proximetacaí-na houve menor queixa de desconforto (sensação de picada e ferroada) com relação ao grupo da tetracaína, com significativa diferença estatística, porém sem perda do efeito analgésico 34 . Ainda, a proximetacaína apresenta menor toxicidade corneana, quando comparada com a oxibuprocaína a 0,4% e lidocaína a 2% a 4% 35,36 . Nesse estudo foi constatada queixa de dor em 42 pacientes, durante o ato operatório, perfazendo um total de 13,5%, diferentemente de dados apresentados na literatura, que registraram um porcentual muito superior, em torno de 60%, dos pacientes submetidos à facectomia com anestesia tó-pica, porém sem sedação, e semelhante a estudos realizados com anestesia retrobulbar 37 e peribulbar 38 .…”
Section: Métodounclassified
“…Para avaliar a segurança da anestesia tópica quando realizada por residentes, foram comparados os dados deste trabalho e também de outros que comparam os dois métodos sendo que com cirurgiões experientes (1)(2)(3) . Os dois grupos apresentavam características demográficas semelhantes.…”
Section: Discussionunclassified
“…Embora sejam eficazes em produzir anestesia e acinesia, estas formas de anestesia local não estão desprovidas de complicações oculares e sistêmicas que ocorrem raramente, mas que podem ser severas. Estas incluem estrabismo, hemorragia retrobulbar, perfuração do globo ocular, e problemas cardiopulmonares (1)(2)(3) . A anestesia tópica para cirurgia de catarata foi possível desde que Koller introduziu a cocaína tópica em 1884.…”
Section: Introductionunclassified